An Eco Friendly Formula for Batik Textiles - Nazlina, Shaari; Khairul Aidil Azlin, A. Rahman (Universiti Malaysia Sarawak, (UNIMAS), 2014)
Batik is one of the world's oldest living crafts and art forms. It has survived so long, adapting and evolving along the way, and still is made in many parts of the world by both traditional and contemporary means suggests it has some wisdom to yield about sustainability. Batik as an everyday item and marker of identity were highly reflecting the Malay culture in the world. Batik represents it multiplicity in use, commodity and gift as well as dominant product of identity. On the other hand, batik usages are the main element for social business. It is also recognized as an art and manners that are favored by each social group that involved with the element sharing of knowledge and values by the society. This knowledge will enhance the development of culture values in representing sustainable identity within the society. It is widely realized that technology has a wide spectrum impact that imposed traditional batik towards modernity. As far as batik represents our culture, sustainability in batik production leads better futures for the batik industries. This paper will discuss on sustainable batik design through environmental concern and its presentation. A wide spectrum impact of batik has shifted form traditional values to modern one comprising eco-friendly formula in batik making process. It is expected that this will create significant impact to the future of batik business.